Korelasi Pengendalian Internal terhadap Opini Audit dan Kinerja Keuangan Perusahaan - Alfita Rakhmayani; Maya Aresteria; Rufi' Ayu Setyoningrum (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Internal control is a mechanism used by the company to achieve its goals. This study examines the relationship between internal control as proxied by the level of disclosure on audit opinion and the company's financial performance. The data is taken from the annual reports of companies that are members of IDX80 in 2020. The test is carried out by correlation using SPSS 25.0. The test results show that the correlation coefficient of internal control with audit opinion is 0.109, while the correlation coefficient with financial performance is 078. The test results show that there is no significant correlation between internal control and audit opinion and financial performance. Disclosure of internal control carried out by the company through its annual report does not necessarily indicate the actual internal control carried out by the company. Disclosure of internal control is only limited to meeting formal requirements so that it will be difficult to predict the company's financial performance through the level of disclosure of internal control it does.